Analysis Evaluation Management Information System Audit Internal Quality - Wulandari, Dewa Ayu Putri; Aristana, Made Dona Wahyu (Journal of Electrical, Electronics and Informatics, 2021)
Information systems are very important in this globalization era. Information systems generally can be used as a reference for decision making or to monitor the progress of an activity process. In high education, information systems are no less important than information systems within the company. Higher education is an institution that uses information systems to monitor work systems to improve quality. Higher Education Institute STMIK STIKOM Indonesia has implemented an internal quality assurance system (SPMI). An example of its application is by carrying out an internal quality audit (AMI). To ensure the quality of the application meets the standards and needs of the user, it can be done by performing software testing based on the ISO 25010 standard .